Review of archaic nymphomyiids (Diptera, Nymphomyiidae) of the Russian Far East and bordering territories, with describing of new taxa and DNA barcoding of known species - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Krasheninnikov, Andrey B.; Yanygina, Lubov V.; Yavorskaya, Nadezhda M. (Zootaxa, 2024)
Nymphomyiidae from the Russian Far East and bordering territories are revised, including data on taxonomy, redescriptions, and results of DNA barcoding. Nymphomyia orientalis sp. nov. with two subspecies N orientalis orientalis subsp. nov. and N. orientalis makcha subsp. nov. are described and information on biology, ecology and distribution are presented. Key of Nymphomyia species for adult males and females of the world is provided. Three species delimitation approaches (ASAP, mPTP, GMYC) using the mitochondrial gene cytochrome c oxidase I (COI) confirm validity of described taxa as well as available nymphomyiids in GenBank. Morphologically indistinguishable specimens of N. orientalis sp. nov. from Makcha and Polovinka rivers belongs to separate mOTUs with the lowest distances in the genus 1.99% that is the lower interspecific threshold.